Personality Profile of Athletes with Disabilities Central Java - Kusumawardhanny, Angga; Sulaiman, Sulaiman; Pramono, Harry (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
The problem of this study is that there is differences that occur because the level of disability of athletes with disabilities such as the training process, skill level, age factors, factors of competitive experience, and the task of movement that must be performed between sports that are differentfrom each. This research is research using mix methods approach. The population of this study is all National Paralympic Committe Indonesia (NPCi) Athletes from central Java from various cities / districts in Central Java. Data collection techniques: questionnaires, questionnaires and interviews. This research instrument uses SPQ 20.. Data analysis techniques; kolmogrov-smirnov test prerequisite test and multi-variate analysis of covariance hypothesis test (mancova)). (1) personality or personality of NPCI athletes with disabilities in Central Java Province in either category; (2) the personality or personality of athletes with physical disabilities is better than that of athletes with sensory disabilities; (3) there are differences in the personality or personality of athletes with physical disabilities with athletes with sensory disabilities with the results of the equal variances assumed sig.2-tailed test 0.042<0.05; (4) the personality or personality of individual sports disability athletes is better than that of group sports disability athletes; (5) there is a difference in the personality or personality of individual sports athletes with group sports athletes with equal variances assumed sig.2-tailed test results of 0.015 < 0.05.